PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. NUSANTARA TROPICAL FARM (NTF) DI LAMPUNG TIMUR - Suwarto, Suwarto (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
The aim to be achieved by the researcher is to determine the influence of Organizational Culture and Leadership Style on Employee Performance at PT.Nusantara Tropical Farm (NTF).The results of this study concluded that the results obtained from Organizational Culture and Leadership Style on Employee Performance at PT. Nusantara Tropical Farm (NTF) is based on the calculation of multiple linear regression tests that variables X1 (Organizational Culture) and X2 (Leadership Style) have a significant influence on employee performance. The existence of a positive relationship between the variables of Organizational Culture (X1) and X2 (Leadership Style) on the Y variable (Employee Performance) means that the variables X1 (Organizational Culture) and X2 (Leadership Style) experience an increase in Y variable (Employee Performance). Vice versa, if the free variable has decreased, it will be followed by a decrease, it will be followed by a decrease in the dependent variable. Variables X1 (Organizational Culture) and X2 (Leadership Style) have a relationship with the Y variable (Employee Performance). This is based on the r hit value that is higher than the r table price.